Proton transport in mesoporous silica SBA-16 thin films with three-dimensional cubic structures - Hwang, Junho (Langmuir : the ACS journal of surfaces and colloids, 2013)
Mesoporous silica SBA-16 thin films with highly ordered 3D cubic structures were synthesized by an evaporation-induced self-assembly method, using an F127 triblock copolymer as the structure-directing agent via dip coating, to investigate the proton transport of aqueous solutions confined in mesopores. Using electrochemical measurements of ionic current under DC electric fields, we elucidated proton transport phenomena through mesopores of SBA-16 thin films. At low concentrations, ranging from 10(-7) to 10(-5) M, the I-V curves of KCl and HCl aqueous solutions were nonlinear. However, at 10(-4) and 10(-3) M, while I-V curves of KCl aqueous solutions displayed nonlinear behavior, those of HCl aqueous solutions were almost linear. The linear behavior can be attributed to a decrease in the electric potential barrier owing to a reduction in the surface charge density, which is caused by the protonation of silanol groups on the inner surface of mesopores. At high concentrations, ranging from 10(-2) to 1 M, the I-V curves of KCl and HCl aqueous solutions were almost linear because the effect of surface charge of mesopores on ion transport was marginal